Strengthening national identity partnerships through community participation in border areas - Bria, Makarius Erwin; Lam, Kee Fui Turner (Jurnal Civics: Media Kajian Kewarganegaraan, 2022)
This study aimed to investigate the participation of border communities in maintaining national identity in the border areas between Indonesia and Timor Leste. The research approach utilized in this study was a case study, and data were collected through interviews, observations, and documentation. The study focused on border communities in East Kobalima District, Malaka Regency, East Nusa Tenggara Province, Indonesia. The findings revealed that border communities participated in maintaining the spirit of nationalism and national identity in three ways. Firstly, they participated in Technical Guidance (Bimtek) on Border Guard Management and capacity building activities for border communities, including the maintenance of national boundary markers such as National Boundary Pillars (PBN) and Border Sign Posts (BSP) along the national border. Additionally, they preserved local culture. Secondly, the community actively participated in flag ceremonies to commemorate the anniversary of the independence of the Republic of Indonesia and National Education Day. Thirdly, they participated in preserving the national language in border areas to communicate with fellow Indonesians and citizens of the Democratic Republic of Timor Leste (RDTL).